E-Modul Interaktif Berbasis Flipbook Maker dalam Pendidikan Multikultural: Integrasi Kearifan Lokal untuk Penguatan Karakter Pancasila Mahasiswa - Bolong, Bertolomeus; Lake, Angelina C. O. R.; Maure, Osniman Paulina (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Multicultural education is very important to strengthen the Pancasila character of students, but the current teaching methods are still theoretical and do not integrate local culture. The purpose of this research is to develop an interactive e-module based on Flipbook Maker for multicultural education courses by integrating the local wisdom of NTT.Method – This study uses the research and development method with the ADDIE development model to design, develop, and test the feasibility of interactive e-modules based on Flipbook Maker. The development process through five stages-analysis, design, development, implementation, and evaluation-was carried out systematically, involving validation by experts and practitioners, as well as descriptive data analysis to assess the quality and feasibility of the e-module. Findings – Validation results showed an average score of 3.307 from media experts, 3.167 from subject matter and language experts, and 3.238 from practitioners, categorizing the e-module as “highly valid” and “valid” with minor revisions. User evaluation yielded an average score of 3.347, confirming that the e-module is suitable for implementation without further revisions. The uniqueness of this e-module lies in its integration of local wisdom from NTT, which has not been incorporated by any previous researchers in the development of multicultural education learning materials. Research Implications – The integration of local wisdom into digital learning media can improve understanding of multicultural education and strengthen students' Pancasila character. Flipbook Maker-based e-modules provide innovative solutions to educational challenges in the digital era. However, its implementation is limited to one university, limiting generalization. In addition, technology access constraints affect effectiveness, and the long-term impact on students' Pancasila character remains unmeasured.